Glow-worm - Heinz Bolten-Backer; Lilla Cayley Robinson (Symphony in the Flint Hills, 2019)
Introduction: Shine little glow-worm, glimmer, glimmer Shine little glow-worm, glimmer, glimmer Lead us lest too far we wander Love’s sweet voice is calling yonder